Measuring signal formation in the bispectral pyrometry - Маркін, Максим Олександрович (Eastern-European Journal of Enterprise Technologies, 2014)
The problem of forming the measuring signal in the bispectral pyrometry is considered in the paper. High-temperature technologies become effective only if the technological requirements are met, that, in its turn, is impossible without appropriate industrial gages. A significant constraint in the field of applying monospectral television measuring devices for controlling temperature modes is the fundamental dependence of measurement results on a priori grounds about the emissivity coefficient of an object and its behavior in the measurement range. In this case, the bispectral pyrometry ensures potentially higher measurement accuracy. But a significant number of issues concerning the bispectral television pyrometry, which are important in theoretical and practical aspects, have not received an adequate interpretation. It means that virtually today there has not been developed potentially the most efficient method for temperature control, which capabilities fully meet the needs of electron-beam technologies for obtaining new materials, laser processing technologies, welding and other related technologies. The analysis of existing circuits of a multispectral signal formation in the pyrometry was made in the paper. There are circuits with light filters deposited on the matrix, using a polygonal prism or bilens. In the paper, it was suggested using a three-layer matrix for forming a multispectral signal. The main advantage of the circuit for forming the measurement signal is high resolution, as well as the absence of such optical system components as light filters, bilens or prism, which complicate the circuit and cause errors in measurements. A physical model of forming measurement and output bispectral pyrometer signals was developed. Using the physical model, a mathematical model was developed. It was concluded that there is a need of further studying properties of bispectral television measuring devices, as well as the influence of slight changes of the emissivity coefficient on errors of temperature measurements.